The mycoheterotrophic genus Didymoplexiella (Orchidaceae) in Cambodia, Laos and Vietnam - Nuraliev, Maxim S.; Averyanov, Leonid V.; Nguyen, Khang Sinh; Nguyen, Cuong Huu; Le, Tuan Anh; Maisak, Tatiana V.; Lyskov, Dmitry F.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P. (Phytotaxa, 2023)
A synopsis of the orchid genus Didymoplexiella is presented for Cambodia, Laos and Vietnam. Uncertainties in morphological delimitation of the species of Didymoplexiella are addressed in the context of the new data on variation of labellum structure; re-identification of a considerable number of specimens is performed in accordance with the current views. Three species are recognised in the study area. Of them, D. laosensis is endemic to Laos and Vietnam; D. ornata is known from Vietnam and also widely distributed in Malesia; and D. siamensis inhabits all three countries of Eastern Indochina and also Thailand, Japan, China and Taiwan. Didymoplexiella laosensis is newly recorded for Vietnam, whereas D. trichechus is excluded from the known flora of Eastern Indochina, and D. ornata is excluded from the flora of Laos. Typification of D. siamensis is revised. For each species, the type, synonyms (where applicable), citations of relevant regional taxonomic publications, brief taxonomic notes, data on ecology, phenology, distribution and IUCN preliminary assessment are provided. The geographical distribution of the species of Didymoplexiella in Cambodia, Laos and Vietnam is shown on a map. A key for the identification of D. laosensis, D. ornata, D. siamensis and D. trichechus is presented.